Substance use among elite adolescent athletes: Findings from the GOAL Study. Issue 1 (9th May 2012) - Diehl, K.; Thiel, A.; Zipfel, S.; Mayer, J.; Schneider, S.
<x xml:space="preserve">Abstract</x> Elite athletes often find themselves in a dilemma between maintaining optimal health to be successful and accepting health risks by pushing their physical limits. For elite adolescent athletes, this dilemma becomes a trilemma as they are also confronted with developmental challenges typical for adolescence. As many adolescents encounter different substances during this critical period of development, we analyzed prevalence of substance use to identify determinants related to these behaviors and to compare the prevalences with nonelite athletes. Our main data were drawn from the German Young Olympic Athletes' Lifestyle and Health Management Study (GOAL Study) including 1138 elite adolescent athletes (14–18 years). For comparisons, the data were combined with data from the German Health Interview and Examination Survey for Children and Adolescents (KiGGS). Beside uni‐ and bivariate analyses, we conducted (conditional) logistic regression analyses. Eighty‐six percent had consumed alcohol at least once. Binge drinking was performed by 24% during the last month. Alcohol consumption was positively associated with age, education, technical sports, lower squads, and attending boarding schools. Binge drinking was higher in males, older adolescents, and in technical sports. Smoking (3%) and marijuana use (3%) were less prevalent. Compared with nonelite athletes, they showed less risky behavior except for binge drinking. As we could identify risk groups, prevention and health promotion programs could be developed for this specific target group.